Fostering Innovation in Startup: The Effect of Psychological Climate on Employees' Innovative Work Behavior - Afifah Ulia Rachmah; Laila Listiana Ulya (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to determine the influence of psychological climate on innovative behavior in startup employees. This research is based on the theoretical assumption that psychological climate represents an individual's subjective perception of the work environment which acts as a psychological mechanism in shaping the response of work attitudes and behaviors. This study uses a quantitative approach with an influence study design, where psychological climate plays a role as an independent variable and innovative behavior as a dependent variable. The research sample consisted of 117 active employees of startup companies in Indonesia with a minimum working period of six months selected through purposive sampling techniques. The data was collected through a five-point Likert scale-based online questionnaire, then tested for validity and reliability before being analyzed using simple linear regression. The results showed that psychological climate had a positive and significant effect on innovative behavior, which was shown by a t-count value of 5.960 with a significance of 0.000 and a positive regression coefficient of 0.392. The R² determination coefficient value of 0.236 indicates that the psychological climate explains 23.6% of the variation in innovative behavior, while the rest is influenced by other factors outside of this study. Overall, this study confirms that the psychological climate is one of the important factors in increasing innovative behavior in startup employees, although innovation is still influenced by various other external factors